Planar Waveguide Optical Sensors From Theory to Applications - Dutta, Aradhana; Deka, Bidyut; Pratim Sahu, Partha (Engineering Materials, 2016)
This book concentrates on the design and development of integrated optic waveguide sensors using silicon based materials. The implementation of such system as a tool for detecting adulteration in petroleum based products as well as its use for detection of glucose level in diabetes are highlighted. The first chapters are dedicated to the development of the theoretical model while the final chapters are focused on the different applications of such sensors. It gives the readers the full background in the field of sensors, reasons for using silicon oxynitride as a potential waveguide material as well as its fabrication processes and possible uses. .